إدارة الصراع وانعكاساتها على الأمن الوظيفي دراسة ميدانية ببلدية المسيلة - حمودي خديجة لمياء; اشراف: زعيتر لامية (جامعة محمد بوضياف -المسيلة, 2025)
تهدف الدراسة الى التعرف والكشف عن أثر إدارة الصراع وانعكاسه على تحقيق الأمن الوظيفي في المؤسسة، ولتحقيق هذا الهدف تم استخدام المنهج الوصفي بأسلوب تحليلي وباستخدام الاستبيان كأداة لجمع البيانات مع المبحوثين في المؤسسة نحل الدراسة وتم تحليلها بواسطة برنامج SPSS v25. تمت الدراسة الميدانية على مستوى مصالح بلدية المسيلة علـى عينـة عشوائية بسـيطة شـملت إداريين ومهنيين بلغت 60 مفردة، وتوصلت الدراسة إلى: • وجوـد علاقــة موجبـة متوسـطة بـين المتغيرين ذات دلالـة إحصائية عنـد مسـتوى (0.05) بين إدارة الصراع والأمن الوظيفي لدى العامل بمصالح البلدية. كما خلصت الدراسة الى أن أبعاد إدارة الصـراع المتـوفرة بمصـالح البلدية مرتبطة بتحقيق الأمن الوظيفي ارتباطا إيجابيا. الكلمات المفتاحية: إدارة الصراع، أسلوب المشاركة، أسلوب التسوية، الأمن الوظيفي. Abstract : The study aims to identify and reveal the impact of conflict management and its impact on achieving job security in the organization; to achieve this goal, the descriptive approach was used in an analytical manner and using the questionnaire as a tool to collect data with the participants in the organization, The study was analyzed using the SPSS v25 program. The field study was conducted at the level of the departments of the municipality of M'sila on a simple random sample that included administrators and professionals, amounting to 60 individuals, The study concluded: • The presence of a positive, average relationship between the two variables with statistical significance at a level of (0.05) between conflict management and job security for the worker in the municipal departments. The study also concluded that the dimensions of conflict management available in municipal departments are positively linked to achieving job security. Keywords: conflict management, participation style, settlement style, job security.